Optimalisasi Pengelolaan Keuangan dan Aset Desa dalam Rangka Meningkatkan Efektivitas Pemerintahan Desa - Firdaus Arifin (Penerbit Goodwood, 2024)
Purpose: The objective of this study is to evaluate and optimize the management of financial balances and village assets in accordance with the principles of state administrative law. Methodology/approach: This study employs a qualitative approach with a normative legal analysis method, as this enables researchers to examine a range of legal sources, including legislation, government regulations, and pertinent policies, and evaluate their compatibility with practices observed in the field. Results: This study emphasizes the importance of policy reform and strengthening administrative capacity at the village level to improve the effectiveness of village governments in managing finances and assets more efficiently and accountably. Limitations: This study is limited to village financial and asset management in Indonesia, which refers to the importance of transparency and accountability. Contribution: This research contributes to the government and village apparatus, policymakers at national and regional levels, and village communities. Furthermore, this research has implications for village development and governance studies, especially in the context of village financial and asset management. Finally, this study contributes to the discipline of state administrative law by providing an in-depth analysis of the implementation of regulations related to village financial and asset management. The research findings highlight the importance of regulatory adaptation based on local context, which is a key aspect of administrative law theory.